Dealing with debt crises in the Eurozone: Evaluation and limits of the European stability mechanism - Sebastian Dullien; Daniela Schwarzer (Stiftung Wissenschaft und Politik (SWP), 2011)
The euro area is still negotiating its future framework for sovereign debt crisis management and prevention. This study suggests what such a framework should look like. As a basic rule, it should distinguish between liquidity problems and solvency problems. In cases of liquidity problems, emergency loans at a low interest rate should be made available. In cases of insolvency, an orderly restructuring of debt should be chosen. However, this is easier said than done as the volumes needed for liquidity support might be very large. Increasing the volume of the European Stability Mechanism (ESM) might endanger France's credit rating. Meanwhile, even an orderly default of a state could trigger a banking crisis. Hence, a five-pillar solution is proposed: First, a permanent liquidity fund with a sufficiently large volume should provide loans to euro area members experiencing acute payment difficulties, with clear conditions and strict budget monitoring. Second, a bank recapitalisation fund should be able to directly inject capital into banks and allow for a restructuring of public debt of one of the euro area countries without having to fear a systemic banking crisis. Third, a debt restructuring mechanism should be introduced for the euro area. Fourth, a euro-bond for up to 60 percent of GDP should make sure that the ESM can remain within a reasonable size and still be able to prevent liquidity support also to large member states. Fifth, substantially strengthened macro-economic and budgetary policy coordination on the EU level based on sound democratic legitimacy would complement the framework. Six case studies show that macroeconomic imbalances are a key factor when assessing solvency and liquidity and hence need to be tackled to ensure the long-term sustainability of the euro area
Keywords: 320